The Use of TikTok Social Media on Students’ Self-Confidence - Erwana Erwana; Dian Fitriani; Nurwahyuni Nurwahyuni; Hasan Hasan (MASI Mandiri Edukasi, 2025)
TikTok has become a popular platform among teenagers as a means of entertainment, self-expression, and social communication. Through its creative features, students can showcase their talents and gain recognition from their peers. However, behind this popularity, the question arises as to whether the use of TikTok can actually boost students’ self-confidence. This study aims to determine the relationship between the use of TikTok social media and the self-confidence of eighth-grade students at SMP Negeri 7 Palu. A total of 100 students were selected using random sampling techniques. Data were collected using a Likert scale-based questionnaire and analyzed both descriptively and inferentially, employing the Pearson Product Moment correlation test in SPSS version 25. The results show that TikTok usage is relatively high at 93%, while student self-confidence is also in the high category at 68%. The correlation test shows a value of r = 0.082 with sig. = 0.418 (p > 0.05), meaning that there is no significant relationship between TikTok usage and student self-confidence. These findings suggest that student self-confidence is more influenced by factors such as family support, social environment, and personal experience, rather than the intensity of TikTok use. These findings suggest that student self-confidence is more influenced by factors such as family support, social environment, and personal experience, rather than the intensity of TikTok use.